2006
DOI: 10.1042/bj20051593
|View full text |Cite
|
Sign up to set email alerts
|

Pyroglutamyl peptidase type I from Trypanosoma brucei: a new virulence factor from African trypanosomes that de-blocks regulatory peptides in the plasma of infected hosts

Abstract: Peptidases of parasitic protozoans are emerging as novel virulence factors and therapeutic targets in parasitic infections. A trypanosome-derived aminopeptidase that exclusively hydrolysed substrates with Glp (pyroglutamic acid) in P1 was purified 9248-fold from the plasma of rats infected with Trypanosoma brucei brucei. The enzyme responsible was cloned from a T. brucei brucei genomic DNA library and identified as type I PGP (pyroglutamyl peptidase), belonging to the C15 family of cysteine peptidases. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…These proteins hydrolyze N-terminal L-pyroglutamyl residues, which confer resistance to the modified peptides from aminopeptidase degradation and in some cases are crucial for biological activity26. A PPI in Trypanosoma brucei has been associated with protection against antimicrobial peptides, suggesting that this enzyme could be an important virulence factor27. However, the corresponding ortholog in L. (L.) major appears to be a key factor during differentiation to metacyclic promastigotes26.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins hydrolyze N-terminal L-pyroglutamyl residues, which confer resistance to the modified peptides from aminopeptidase degradation and in some cases are crucial for biological activity26. A PPI in Trypanosoma brucei has been associated with protection against antimicrobial peptides, suggesting that this enzyme could be an important virulence factor27. However, the corresponding ortholog in L. (L.) major appears to be a key factor during differentiation to metacyclic promastigotes26.…”
Section: Resultsmentioning
confidence: 99%
“…Presumably, the major function of the pGlu residue is to provide stability against degradation by aminopeptidases, thus prolonging the physiological half-life of these peptides (30). For several hormones, a crucial role of the N-terminus for binding to the respective receptor is described (31).…”
Section: Discussionmentioning
confidence: 99%
“…Quite surprisingly, activation of a T. brucei CP by a kininogen-like molecule from rat serum (called rat trypanopain modulator) has also been reported (69). Recently, the first report of the in vivo activity of bloodstream-released CP has been published with a description of a pyroglutamyl peptidase (PGP) type I from T. brucei brucei (96). In that study, this enzyme showed optimal activity at bloodstream pH and proved to be insensitive to plasma CP inhibitors.…”
Section: The Major Candidatesmentioning
confidence: 99%